2009
DOI: 10.1038/ncb1861
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D1 regulates cofilin-mediated F-actin reorganization and cell motility through slingshot

Abstract: Dynamic actin remodelling processes at the leading edge of migrating tumour cells are concerted events controlled by a fine-tuned temporal and spatial interplay of kinases and phosphatases. Actin severing is regulated by ADF/Cofilin which regulates stimulus-induced lamellipodia protrusion and directed cell motility. Cofilin is activated by dephosphorylation via phosphatases of the slingshot (SSH) family. SSH activity is strongly increased by its binding to filamentous actin (F-actin), however, other upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
317
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(335 citation statements)
references
References 45 publications
15
317
1
Order By: Relevance
“…The activity of cofilin is controlled by phosphorylation and dephosphorylation on serine-3 of cofilin by LIMK and Slingshot-1L (SSH), respectively. 14,15 Consistent with the role of RanBP9 in focal adhesion disruption, 9 cofilin levels were dramatically enhanced (Figures 7a and b), and serine-3 phosphorylated cofilin levels were reduced after RanBP9 transfection (Figure 7a). Therefore, RanBP9 significantly reduced the level of phosphocofilin per total cofilin to less than 15% of control-transfected cells (Figure 7c).…”
Section: Wt Ranbp9 Tgsupporting
confidence: 58%
“…The activity of cofilin is controlled by phosphorylation and dephosphorylation on serine-3 of cofilin by LIMK and Slingshot-1L (SSH), respectively. 14,15 Consistent with the role of RanBP9 in focal adhesion disruption, 9 cofilin levels were dramatically enhanced (Figures 7a and b), and serine-3 phosphorylated cofilin levels were reduced after RanBP9 transfection (Figure 7a). Therefore, RanBP9 significantly reduced the level of phosphocofilin per total cofilin to less than 15% of control-transfected cells (Figure 7c).…”
Section: Wt Ranbp9 Tgsupporting
confidence: 58%
“…This may be an important goal for future therapeutics as there is emerging evidence that PKD isoforms play different roles in tumors of different origin. For example, a series of studies by Eiseler and coworkers found that PKD1 negatively regulates migration of Panc89 cells through several related mechanisms including association of PKD with F-actin and phosphorylation of cortactin and slingshot 1 (SSH1) (42)(43)(44). In addition, PKD1 expression is decreased in invasive breast cancers and expression of a constitutively active PKD1 mutant decreased the invasiveness of MDA-MB-231 breast carcinoma cells by causing a subsequent decrease in matrix metalloproteinase expression (45).…”
Section: Pkd and Tumor Angiogenesismentioning
confidence: 99%
“…PKD localizes to sites of dynamic actin remodeling (1). The kinase activity is essential for the control of directed cell motility (1,2), whereby active PKD1 inhibited, whereas kinase-inactive PKD1KD strongly enhanced motility and invasiveness (1)(2)(3)(4). Mechanistically, a key role for PKD1 in controlling the activity of the ubiquitous F-actin depolymerizing-and severing factor cofilin via slingshot1L (SSH1L) cofilin phosphatase has been demonstrated.…”
mentioning
confidence: 99%
“…Protein kinase D (PKD) 2 has recently been identified as a vital upstream regulator of polarized cell motility and F-actin organization (1)(2)(3)(4). PKD localizes to sites of dynamic actin remodeling (1).…”
mentioning
confidence: 99%